Sero-Prevalence of Brucellosis in Small Ruminants of Erstwhile Guntur District, Andhra Pradesh - B. SreeLakshmi; K. Lavanya; A. Gurava Reddy (The Indian Veterinary Journal, 2025)
A study was conducted to determine the sero-prevalence and to delineate the risk factors for Brucella seropositivity in small ruminants of erstwhile Guntur district, Andhra Pradesh. In the present study, a total of 1033 sera samples from small ruminants (798 sheep and 235 Goat) of erstwhile Guntur district were screened using Rose Bengal Plate Test (RBPT) and Indirect Enzyme Linked Immuno sorbent Assay (I- ELISA). Overall Sero-prevalence of Brucellosis in small ruminants was 8% and 21.3% on RBPT and I-ELISA respectively. The prevalence was more in adults (43.9%) than younger ones and more in females (21.8%) than male (19.9%) on I-ELISA.